Islamic finance education curriculum development in Malaysia - Alhabshi, Syed Musa (ABRN Asia, 2021)
Islamic Finance as a discipline has evolved from different disciplines to meet the financial sector expectations in terms of socio-technical competencies. Various initiatives from both regulatory and governing agencies have attempted to shape the nature and direction of Islamic finance as both academic and professional programs are promulgated by Institutions of higher learning and training providers. This study explores and discusses both the interdisciplinary and multidisciplinary curriculum development approaches to Islamic finance education and its potential impact on program quality assurance and competency in the Islamic financial services industry and community.